Review of alternative practices to cigarette smoking and nicotine replacement therapy: How safe are they? - O.B. Omole; G.A. Ogunbanjo; O.A. Ayo-Yusuf (South African Family Practice)
Most adverse health effects of cigarette smoking are attributed to the products of combustion. Efforts to avoid the adverse health effects of cigarette smoking have led to the promotion of alternative products that are perceived to be less harmful. In this paper, we review the available literature for evidence of the effectiveness of the products commonly presented as alternatives to cigarette smoking, and discuss evidence-based information on whether they should be promoted as safe alternatives for long-term use or are effective as cessation aid. Water pipe smoking is becoming prevalent among young people and the electronic cigarette has been recently introduced as smoking alternative in smoke-free areas. Available limited data suggest that while smokers may perceive these alternatives as safer than cigarette smoking, they contain toxic substances and therefore are not harmless alternatives. Data on herbal products are not easily available and where they are, evidence shows that these products are also not effective alternatives. Smokeless tobacco products vary in composition and health effects worldwide. The available literature suggests that these products may be associated with adverse health outcomes and that they cannot be promoted as ‘safe’ alternative tobacco products. Nicotine replacement therapy (NRT) formulations, such as chewing gums and skin patches, have been well studied and evidence suggests that all forms are effective smoking cessation aids, either used alone and in combination with other NRT or cessation medication and behavioural therapy. Primary care physicians should therefore only offer NRT to smokers who are willing to quit in combination with behavioural therapy or other cessation medications approved by the South African Medicines Control Council.